2016
DOI: 10.1039/c6pp00304d
|View full text |Cite
|
Sign up to set email alerts
|

A novel photosensitizer: An l-glutamide lipid conjugate with improved properties for photodynamic therapy

Abstract: Photosensitizers (PS) are used in photodynamic therapy to treat several cancers. The efficacy of photodynamic therapy (PDT) could be further improved by overcoming aggregation-dependent quenching of PS and by improving the biodistribution of the PS. In this work we attempted to overcome these issues by conjugating a PS with a lipid molecule and tested the liposomes prepared with this PS conjugated lipid for PDT. A novel lipid-porphyrin conjugate (1 : 1) was synthesized by attaching a PS, 5-(4-methoxycarbonylph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…Without the stable membrane insertion of BPD into the nanoconstruct, attempts at antibody targeted delivery of BPD become futile. Lipidic bilayered nanovesicles formed of lipidated porphyrins, first reported in 2002, 49 have been previously prepared by the conjugation of porphyrins to phospholipid acyl chains, 49 glycerol moieties, 48,50,51 phosphate head groups, 52,53 and PEG chains. 48,54 Recent studies by Zheng and Lovell have demonstrated the unique properties of lipidated porphyrin constituents of nanomedicines and nanotheranostics.…”
Section: Nano Lettersmentioning
confidence: 99%
See 1 more Smart Citation
“…Without the stable membrane insertion of BPD into the nanoconstruct, attempts at antibody targeted delivery of BPD become futile. Lipidic bilayered nanovesicles formed of lipidated porphyrins, first reported in 2002, 49 have been previously prepared by the conjugation of porphyrins to phospholipid acyl chains, 49 glycerol moieties, 48,50,51 phosphate head groups, 52,53 and PEG chains. 48,54 Recent studies by Zheng and Lovell have demonstrated the unique properties of lipidated porphyrin constituents of nanomedicines and nanotheranostics.…”
Section: Nano Lettersmentioning
confidence: 99%
“…Without the stable membrane insertion of BPD into the nanoconstruct, attempts at antibody targeted delivery of BPD become futile. Lipidic bilayered nanovesicles formed of lipidated porphyrins, first reported in 2002, have been previously prepared by the conjugation of porphyrins to phospholipid acyl chains, glycerol moieties, ,, phosphate head groups, , and PEG chains. , Recent studies by Zheng and Lovell have demonstrated the unique properties of lipidated porphyrin constituents of nanomedicines and nanotheranostics. , We thus synthesized a panel of liposomal nanoformulations of BPD and its lipidated variants conjugated to 16:0 lyso PC, 20:0 lyso PC, and cholesterol through Steglich esterification or to DSPE-PEG 2000 -NH 2 by EDC-amide coupling . Cholesterol was selected as a classical membrane anchor, 16:0 lyso PC and 20 lyso PC were compared for their varying acyl chain length, and DSPE-PEG 2000 -NH 2 was selected for its double acyl chain membrane anchors.…”
mentioning
confidence: 99%
“…Hence, the DOX drug will be released, and the fluorescence of the porphyrin will be recovered. Nathan et al [96] have also shown that the modification of porphyrins using a L-glutamide lipid chain led to the formation of porphysomes with better PDT efficiency compared to the usual liposomal formulations.…”
Section: Porphysomes For Cancer Theranosticsmentioning
confidence: 99%